2005
DOI: 10.1136/adc.2004.066589
|View full text |Cite
|
Sign up to set email alerts
|

Temperature variation in newborn babies: importance of physical contact with the mother

Abstract: Background: Hypothermia is a major cause of deterioration and death in the neonatal period. Temperature deviations are key signs of illness. Objective: To determine normal patterns of temperature variation in newborn babies and the influence of external factors. Methods: Abdominal and foot skin temperature were continuously recorded in 27 healthy full term babies during the first two days of life and related to the care situation-that is, whether the baby was with the mother or in its cot. The recordings were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 11 publications
(12 reference statements)
4
28
0
4
Order By: Relevance
“…One of the prime indicators that proximity is at a neutral, and desired, level is body temperature. That is, Fransson, Karlsson, and Nilsson (2005) found that babies have smaller differences between skin temperature and core temperature when being held (vs. when not) potentially preventing hypothermia, and thus maintaining homeostasis.…”
Section: Further Distinguishing Humans From Penguins: Thermoregulatiomentioning
confidence: 99%
“…One of the prime indicators that proximity is at a neutral, and desired, level is body temperature. That is, Fransson, Karlsson, and Nilsson (2005) found that babies have smaller differences between skin temperature and core temperature when being held (vs. when not) potentially preventing hypothermia, and thus maintaining homeostasis.…”
Section: Further Distinguishing Humans From Penguins: Thermoregulatiomentioning
confidence: 99%
“…Current information on incidence of hypothermia is based on the studies conducted in controlled environment of DRs from the developed countries [3][4][5][6] and from a few other studies conducted in PNWs 8,9,12 and communities of developing countries. [15][16][17][18][19][20] No information is available on thermal adaptation immediately after birth of infants who are delivered in hospitals and PHCs in countries with limited resources to maintain controlled room temperature and humidity as per standard guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] These studies were mainly carried out in a controlled optimal environment. 6,7 In contrast, in developing countries the environment in the delivery rooms (DRs) is uncontrolled. 8,9 Studies in developing countries, including India, have demonstrated high incidence of hypothermia in neonatal period.…”
Section: Introductionmentioning
confidence: 99%
“…That is, Fransson et al (2005) found that babies have smaller differences between skin temperature and core temperature when being held (vs. when not) potentially preventing hypothermia. Additionally, skin-to-skin contact leads the feet of neonates (that were skinto-skin, as compared to those that were removed from the skin of the mother and swaddled) to have a greater increase in skin temperature (Bystrova et al, 2007; for a summary see IJzerman et al, 2015b).…”
Section: Is Attachment Radically Embodied?mentioning
confidence: 99%